EFEKTIFITAS PENGELOLAAN FASILITAS BELAJAR DI PERPUSTAKAAN - Jamaluddin Jamaluddin (Idaarah: Jurnal Manajemen Pendidikan, 2018)
The purpose of this article is to provide readers with understanding of the effectiveness of the management of library learning facilities. To produce a quality education system, not only seen in one aspect only but covering various aspects of other support such as teachers, libraries management, financial support, and information technology. In addition, Human resources, also has an important role to make learning facilities more efective use, for including competence, skills, abilities, attitudes, behavior, motivation, and commitment.